Influence of shear velocity on frictional characteristics of rock surface - Singh T.N.; Verma A.K.; Kumar T.; Dutt A. (My University, 2025)
Understanding the fundamental issues related with the effect of shear velocity on frictional characteristics at the interface of rock surfaces is an important issue. In this paper, strain-rate dependence on friction is investigated in relation to sliding behaviour under normal load. The phenomenon of stick-slip of granite and shaly sandstone with a tribometer at constant rate of strain under normal loads was observed. Friction at the interface of the rock samples was developed by increasing shear strain at a constant rate by applying constant velocity using the tribometer. For shaly sandstone, state parameters (a and b) played a major role in determining the friction values and roughness of the contact surfaces as well. Higher values of b for shaly sandstone may be attributed to the fact that its surface had a greater number of pronounced asperities. Rubbing between the surfaces does not mean that surface becomes smoother. This is because of variation of friction between surfaces. © Indian Academy of Sciences.